The Application of Homer Optimization Software to Investigate the Prospects of Hybrid Renewable Energy System in Rural Communities of Sokoto in Nigeria - Abdullahi Abubakar Masud (International Journal of Electrical and Computer Engineering (IJECE), 2017)
This paper investigates the prospects and cost-effectiveness of implementation of standalone PV/wind system in sokoto state Nigeria. Daily electricity demand, yearly solar radiation and wind speed were applied to determine the optimum sizing of the renewable energy (RE) system. To design optimum RE with proper sizing of system components, meteorological data obtained from the National Aeronautics and Space Administration were applied as input for this study. In Nigeria, sokoto is a region with solar radiation of 6kWh/m2/day and wind speed of 5m/s at 10m above height. Using the Homer optimization software, the optimum integrated RE system is 35.21kW PV, 3 x 25kW wind turbines, 12 x 24V lead acid battery and 17.44kW converter. The system has a total capital cost of $249910.24, the replacement cost of $82914.85 and maintenance cost of $53802.80 for 25 years. Though the initial capital cost is high but the long term benefits are enormous, considering the high cost of implementing rural electrification scheme, coupled with ahike in electricity tariff. There is also a payback period of 5 years. The results imply a standalone PV/wind system is feasible in rural communities of sokoto with 100% pollution free energy system.